A model-based sustainable productivity concept for the best decision-making in rough milling operations. (December 2021) - Urbikain Pelayo, G.; Olvera-Trejo, D.; Luo, M.; Tang, K.; López de Lacalle, L.N.; Elías-Zuñiga, A.
Graphical abstract: Highlights: A tool for improved decision-making in rough milling processes. New approach based on an indicator considering productivity and sustainability. Bottom-up approach based on force and power modelling. Case study (milling tests) applied to serrated, trochoidal and plunge milling. Abstract: There is a need in manufacturing as in machining of being more productive. However, at the same time, workshops are also urged for lesser energy waste in cutting operations. Specially, rough milling of impellers and bladed integrated disks of aircraft engines need an efficient use of energy due to the long cycle times. Indeed, to avoid dramatic tool failures and idle times, cutting conditions and operations tend to be very conservative. This is a multivariable problem, where process engineers need to handle several aspects such as milling operation type, toolpath strategies, cutting conditions, or clamping systems. There is no criterion embracing productivity and power consumption. In this sense, this work proposes a methodology that meets productivity and sustainability by using a specific cutting energy or sustainable productivity gain (SPG) factor. Three rough milling operations -slot, plunge nad trochoidal milling- were modelled and verified. A bottom-up approach based on data from developed mechanistic force models evaluated and compared different alternatives for making a slot, which is a common operation in that king of workpieces. Experimental data confirmed that serrated end milling with the highest SPG value of 1 is the best milling operation in terms of power consumption and mass removal rate (MRR). In the case of plunge milling technique achieve an SPG < 0.51 while trochoidal milling produces a very low SPG value.